Assessment Tools for Post-Stroke Discharge Readiness: A Literature Review - Afrizal Nur Kadir; Yurike Septianingrum; Arvino Aprilian; Lono Wijayanti; Umdatus Soleha (Indonesian Journal of Global Health Research, 2025)
Stroke survivors are at high risk of hospital readmission due to recurrent stroke, comorbidities, and inadequate discharge preparation. Readiness for hospital discharge plays a pivotal role in ensuring a safe transition of care and improving post-stroke outcomes. Evaluating patient and caregiver readiness for hospital discharge is essential to reduce the likelihood of readmission and optimize home care outcomes. This review aimed to identify, describe, and evaluate existing tools used to assess discharge readiness in post-stroke patients, and examine their effectiveness in supporting care transitions and preventing hospital readmissions.Methods: A systematic review was conducted in accordance with PRISMA guidelines. Four databases-PubMed, Science Direct, Clinical Key, and Google Scholar—were searched for relevant articles published between 2021 and 2025 using predefined keywords related to stroke, discharge readiness, transition of care, and readmission. After screening 202 initial records, 34 articles were selected for full-text review. Ten studies met the inclusion criteria and were then critically appraised using the Joanna Briggs Institute (JBI) checklist to assess methodological quality and risk of bias. The included studies were synthesized narratively based on study design, assessment tools used, psychometric properties, and their impact on discharge readiness and hospital readmission outcomes. The review identified several validated tools, including the Readiness for Hospital Discharge Scale (RHDS), the Preparedness Assessment for the Transition Home After Stroke (PATH-s), and the Caregiver Contribution to Self-Care Inventory (CC-SC-CII-v2). These tools varied in focus, population, and application context. While some showed strong psychometric properties and predictive power for readmission, others highlighted the need for caregiver inclusion and context-specific adaptation. However, inconsistencies in implementation, limited integration into clinical workflows, and lack of long-term outcome evaluations remain significant barriers. This review enhances understanding of discharge readiness assessment tools in post-stroke care and underscores their value in reducing readmissions and optimizing care transitions.